(untitled) (Conference on English Language Teaching, 2025)
This study examines how ChatGPT uses references to other literary works when interpreting classic poems and assesses its usefulness in teaching English literature to students learning English as a Foreign Language (EFL). Using a qualitative method called directed content analysis, the research analyzed ChatGPT’s responses to three well-known poems: Shakespeare’s Sonnet 18, Robert Frost’s The Road Not Taken, and Percy Bysshe Shelley’s Ozymandias. The analysis focused on four main areas: (1) identifying poetic elements like imagery, word choice, structure, and symbolism; (2) exploring connections to other texts through references, imitations, or changes; (3) evaluating how ChatGPT’s responses could help in EFL classrooms by providing interactive feedback and encouraging discussion; and (4) considering the limitations of ChatGPT’s interpretations. The findings show that ChatGPT effectively identifies key poetic features and draws meaningful connections to other literary works. Its responses can serve as helpful examples for close reading and support literature discussions in EFL settings, aiding students in developing critical thinking and expanding their literary vocabulary. However, ChatGPT often presents a single, fixed interpretation, highlighting the need for teachers to guide students toward considering multiple perspectives. In conclusion, ChatGPT has significant potential as a teaching tool for EFL literature classes, especially in supporting the analysis of literary connections, provided that educators facilitate critical discussions and encourage diverse interpretations.